2021
DOI: 10.1177/2399808321991540
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal dynamics of flood exposure in Shenzhen from present to future

Abstract: The Pearl River Delta metropolitan region is one of the most densely urbanized megapolises worldwide with high exposure to weather-related disasters such as storms, storm surges and river floods. Shenzhen megacity has been the fastest growing city in the Pearl River Delta region with a significant increase of resident population from 0.32 million in 1980 to 13.03 million in 2018. Being a flood-prone city, Shenzhen’s rapid urbanization has further exacerbated potential flood losses and forthcoming risk. Thus, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…However, the in uence factors involved in ood risk and the ood risk process are uncertain and ambiguous. Fuzzy comprehensive evaluation method can solve these problems very well and is suitable for risk evaluation with fuzzy and uncertain characteristics (Cai et al 2019, Lai et al 2020, Sarica et al 2021, Zadeh 1965. After collecting all factor data in Table 1 and referring to the research results of Huang andLi (2021) and Abdalla et al (2014), the fuzzy comprehensive evaluation is used to assess urban rainstorm-induced ood risk in the study area, the speci c process is shown in Fig.…”
Section: Rainstorm-induced Flood Risk Assessment Methodsmentioning
confidence: 99%
“…However, the in uence factors involved in ood risk and the ood risk process are uncertain and ambiguous. Fuzzy comprehensive evaluation method can solve these problems very well and is suitable for risk evaluation with fuzzy and uncertain characteristics (Cai et al 2019, Lai et al 2020, Sarica et al 2021, Zadeh 1965. After collecting all factor data in Table 1 and referring to the research results of Huang andLi (2021) and Abdalla et al (2014), the fuzzy comprehensive evaluation is used to assess urban rainstorm-induced ood risk in the study area, the speci c process is shown in Fig.…”
Section: Rainstorm-induced Flood Risk Assessment Methodsmentioning
confidence: 99%
“…However, the in uence factors involved in ood risk and the ood risk process are uncertain and ambiguous. Fuzzy comprehensive evaluation method can solve these problems very well and is suitable for risk evaluation with fuzzy and uncertain characteristics (Cai et al 2019, Lai et al 2020, Sarica et al 2021, Zadeh 1965. After collecting all factor data in Table 1 and referring to the research results of Huang andLi (2021) and Abdalla et al (2014), the fuzzy comprehensive evaluation is used to assess urban rainstorm-induced ood risk in the study area, the speci c process is shown in Fig.…”
Section: Rainstorm-induced Flood Risk Assessment Methodsmentioning
confidence: 99%
“…This indicates the increment of people settlement on the outer city region at the cost of agriculture and fallow land (Mekonnen and Ghosh 2020). Various analysis took place regarding sensitivity and other calibration best fit values over the years (Saxena et al 2021b;Sarica et al 2021;Zhang et al 2021;Jat and Saxena 2021). The road network gravity factor was also prominent for horizontal urban growth development.…”
Section: Model Predictionmentioning
confidence: 99%